Is there a polynomial D(2X + 1)-quadruple? - Franušić Zrinka; Jurasić Ana (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica)
In this paper, we show that there does not exist a polynomial D(2X+ 1)-quadruple {a, b, c, d}, such that 0 < a < b < c < d and deg d = deg b.